Effect of atmosphere and dopants on sintering of SnO2 - Varela J.A.; Perazolli L.A.; Longo E.; Leite E.R.; Cerri J.A. (Science of Sintering, 2002)
Tin oxide is an n type semiconductor material with a high covalent behavior. Mass transport in this oxide depends on the surface state promoted by atmosphere or by the solid solution of aliovalent oxide doping. The sintering and grain growth of this type of oxide powder is then controlled by atmosphere and by extrinsic oxygen vacancy formation. For pure SnO2 powder the surface state depends only on the interaction of atmosphere molecules with the SnO2 surface. Inert atmosphere like argon or helium promotes oxygen vacancy formation at the surface due to reduction of SnO2 to SnO at the surface and liberation of oxygen molecules forming oxygen vacancies. As a consequence surface diffusion is enhanced leading to grain coarsening but no densification. Oxygen atmosphere inhibits SnO2 reduction by decreasing the surface oxygen vacancy concentration. Addition of dopants with lower valence at the sintering temperature creates extrinsic charged oxygen vacancies that promote mass transport at the grain boundary leading to densification and grain growth of this polycrystalline oxide.